Applying of B-mode ultrasound for determining pregnancy by means of measurement of Placentomes Diameter and Fetal Bi-parietal diameter in dairy cows - Rasheed, Yaseen Mahmood (The Iraqi Journal of Veterinary Medicine, 2019)
The objective of the current study was to estimate whether fetal age could be accurately estimated using trans-rectal and trans-abdominal ultrasonographic measurements for placentomes diameter and Bi-parietal diameter. This experiment was carried out in the College of Veterinary Medicine in Diyala University. Twelve Multiparous cows (4-7 years old) were inseminated artificially and Serial transrectal and trans-abdominal ultrasonic examinations were done during the 7 – 13 week and during 10 -26th week of gestation, respectively. Using 5-7.5 MHz linear array transducer and also 3.5-5MHz convex transducer. Possible discrimination of placentomes and Bi-parietal diameter for the first time at the fifth and ninth week of gestation, respectively. The mean values for placentomes diameter were 7.5mm and 69 mm during 7 and 26 weeks of pregnancy, respectively, as well the placentome increased in diameter an average of 3.0028 mm per week. Besides that, the mean Bi-parietal diameter was 17.5mm and 33mm during 9 and 13 week of pregnancy, respectively. The Bi-parietal diameter was increased linearly an average of 3.620 mm per week. The obtained results revealed that using Trans-rectal ultrasonic during 3rd month of gestation to observed pregnancy and fetal organs as well as fetal viability with fast and easy during mid-gestation onward High correlations were found between different studied parameters and gestational age with high significant for both which were (R=0.97**; P<0.01) and(R=0.95**; P<0.01) for placentomes diameter and Bi-parietal diameter respectively. In conclusion, the trans-abdominal ultrasonography it reliable technique for determining pregnancy and the best window for fetal viability during third month of gestation until term and a strong positive with a high significant correlation of coefficient between gestational periods and placentomes diameter, fetal bi-pareital diameter in cows and relatively the highest correlation was also evident in placenttomes diameter, moreover, this study prove that widely restricted factors of ultrasound are that its efficient, is always depending on skill of the operator